Sarnath : A Critical History of the Place Where Buddhism Began - Asher, Frederick M. (Book collections on Project MUSE., 2020)
"This volume provides an analytical history of Sarnath, the place where the Buddha preached his first sermon and established the Buddhist monastic order. Excavations at Sarnath have yielded the foundations of temples and monastic dwellings, two stupas, and some of the most important sculptures in the history of Indian art"--